1999
DOI: 10.1002/(sici)1522-7278(199902)14:1<163::aid-tox21>3.3.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Deoxycylindrospermopsin, an analog of cylindrospermopsin from Cylindrospermopsis raciborskii

Abstract: () ABSTRACT: Cylindrospermopsin CYN is a hepatotoxic alkaloid found in the blue -green alga Cylin-( ) drospermopsis raciborskii C. raciborskii . Data indicating CYN alone does not account for the toxicity of freeze dried cultures of C. raciborskii have been presented recently. In an attempt to explain these data, we have purified and characterized the structure of an analog of CYN, deoxycylindrospermopsin ( ) ( ) deoxy-CYN . Three mice dosed intraperitoneally IP with 0.8 mg/ kg of deoxy-CYN showed no toxicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
68
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(76 citation statements)
references
References 0 publications
5
68
0
3
Order By: Relevance
“…A Fugue search and an iterated Psi-BLAST revealed that CyrI is similar to a hydroxylase belonging to the 2-oxoglutarate-and Fe(II)-dependent oxygenase superfamily, which includes the mammalian prolyl 4-hydroxylase alpha subunit, which catalyzes the hydroxylation of collagen. We propose that CyrI catalyzes the hydroxylation of C-7, a residue that along with the uracil ring seems to confer much of the toxicity of cylindrospermopsin (28). This is supported by the feeding experiments showing that the hydroxyl group at C-7 of cylindrospermopsin is not of acetate origin.…”
Section: The Mt Domain Identified In Cyrb Via the Nrps/pks Databases mentioning
confidence: 99%
“…A Fugue search and an iterated Psi-BLAST revealed that CyrI is similar to a hydroxylase belonging to the 2-oxoglutarate-and Fe(II)-dependent oxygenase superfamily, which includes the mammalian prolyl 4-hydroxylase alpha subunit, which catalyzes the hydroxylation of collagen. We propose that CyrI catalyzes the hydroxylation of C-7, a residue that along with the uracil ring seems to confer much of the toxicity of cylindrospermopsin (28). This is supported by the feeding experiments showing that the hydroxyl group at C-7 of cylindrospermopsin is not of acetate origin.…”
Section: The Mt Domain Identified In Cyrb Via the Nrps/pks Databases mentioning
confidence: 99%
“…[106]. CYN has two known derivatives, one of them is toxic, 7-epicylindrospermopsin [1] and the other virtually nontoxic, deoxy-cylindrospermosin [86].…”
Section: Cylindrospermopsinsmentioning
confidence: 99%
“…One of these analogues is 7-epi-CYN, a C-7 epimer of CYN with toxicity similar to CYN (2). The other is 7-deoxy-CYN, which lacks the hydroxyl group on C-7 and shows no toxicity to mice by intraperitoneal injection (35). In another study, however, 7-deoxy-CYN was proven to be a potent inhibitor of protein synthesis in vitro, and oxygenation at C7 was not essential for its toxicity (27).…”
mentioning
confidence: 99%